Penerapan Augmented Reality Berbasis Android Sebagai Bahan Ajar Untuk Pemodelan Mesin Injection - Alvino Octaviano; Sofa Sofiana (Teknik Informatika Universitas Pamulang, 2018)
The value obtained by Fadilah Vocational School students about motorcycle injection systems is still below the value of mastery learning. Many factors cause students to get low scores in the competence to understand the gasoline fuel system, especially the Honda motorcycle injection system. One of the factors that makes it difficult for students to understand injection material is the unavailability of Honda PGM-FI system props. The limited number of teaching aids is a shortage of private schools in general due to the limited costs of procuring teaching aids for the PGM-FI system. Less interesting learning model is also a factor in the low value of students in certain subjects. Augmented Reality is a developing technology in the world, combining two-dimensional or three-dimensional virtual objects into a real three-dimensional environment and then projecting these virtual objects in real time. Three dimensions commonly abbreviated as 3D, or space, are forms of objects that have length, width, and height. This term is usually used in the fields of art, animation, computers and mathematics. The application of Augmented Reality is not like virtual reality that completely replaces reality, but only adds or completes reality by using libraryVuforia, the image in the form of three dimensions will appear on the screen of the Android smartphone assisted by the rear camera. The application of Augmented Reality in learning is more interesting because this technology provides real visualization. So that learning in the field of education is more interesting and uses the latest technology so that students are more interested in learning.